2006
DOI: 10.1586/14779072.4.6.801
|View full text |Cite
|
Sign up to set email alerts
|

The osteoprotegerin/RANK/RANKL system: a bone key to vascular disease

Abstract: Owing to the common coincidence of osteoporosis and vascular disease, pathophysiological links between both disorders have long been sought. The osteoprotegerin (OPG)/receptor activator of NF-kappaB (RANK)/receptor activator of NF-kappaB ligand (RANKL) cytokine network, a key regulatory system in bone homeostasis, has been implicated recently in vascular calcification, changes in matrix composition and diabetic macroangiopathy, aortic aneurysm development, heart failure and, most importantly, advanced atherosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
0
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(134 citation statements)
references
References 83 publications
3
119
0
12
Order By: Relevance
“…In in vitro studies, osteoprotegerin was found to inhibit calcification in vascular smooth muscle cells70 and act as a survival factor in endothelial cells 71. In contrast, several lines of evidence from experimental studies in animals and cell cultures suggested harmful effects of osteoprotegerin in agreement with the positive association with CVD risk in our meta‐analysis 6. Osteoprotegerin not only contributes to systemic inflammation,72 but also to vasculature‐specific inflammation by increasing macrophage infiltration73 and leukocyte adhesion to endothelial cells 74, 75.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In in vitro studies, osteoprotegerin was found to inhibit calcification in vascular smooth muscle cells70 and act as a survival factor in endothelial cells 71. In contrast, several lines of evidence from experimental studies in animals and cell cultures suggested harmful effects of osteoprotegerin in agreement with the positive association with CVD risk in our meta‐analysis 6. Osteoprotegerin not only contributes to systemic inflammation,72 but also to vasculature‐specific inflammation by increasing macrophage infiltration73 and leukocyte adhesion to endothelial cells 74, 75.…”
Section: Discussionsupporting
confidence: 86%
“…In addition to its role in bone homeostasis, osteoprotegerin has been implicated in the development of cardiovascular diseases (CVDs) 6. It is found in atherosclerotic plaques,7, 8 may regulate vascular calcification,9, 10 and may thereby influence cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies indicate that the level of soluble RANKL is lower in those on statin therapy than in those not on statin therapy. 26 Women taking statins have a higher bone density than those who do not. 52 In experimental rabbit aortic valve calcification, bone-matrix deposition is reduced by atorvastatin.…”
mentioning
confidence: 99%
“…33,34 A previous study demonstrated both RANKL and OPG expression in nondiseased and early atherosclerosis. Interestingly, in calcified areas of advanced atherosclerotic lesions, OPG was expressed within the calcified areas with the RANKL in the areas surrounding them.…”
Section: Discussionmentioning
confidence: 98%